The COVID-19 Cytokine Storm; What We Know So Far - Ragab, Dina; Salah Eldin, Haitham; Taeimah, Mohamed; Khattab, Rasha; Salem, Ramy (Frontiers in Immunology, 2020)
COVID-19 is a rapidly spreading global threat that has been declared as a pandemic by the WHO. COVID-19 is transmitted via droplets or direct contact and infects the respiratory tract resulting in pneumonia in most of the cases and acute respiratory distress syndrome (ARDS) in about 15 % of the cases. Mortality in COVID-19 patients has been linked to the presence of the so-called “cytokine storm” induced by the virus. Excessive production of proinflammatory cytokines leads to ARDS aggravation and widespread tissue damage resulting in multi-organ failure and death. Targeting cytokines during the management of COVID-19 patients could improve survival rates and reduce mortality.